Estrutura organizacional versus desempenho profissional. Estudo de caso de uma autarquia federal - Sá, Jairo Corrêa de (2001)
During the 1980¿s and the 1990¿s, the Brazilian federal government started to set up a new public administration policy called ¿managerial¿ conceived of new patterns of efficiency and effectiveness and extremelly concerned about optimizing state administration to grant best results for people. This decision has been taken due to three main reasons; (i) the worst fiscal crisis considering the last decades; (ii) exhaustion on interfering with Brazilian economy due to its opening to globalization, and (iii) extremelly deep-rooted burocratic methods. The Brazilian state reform presented as a diagnosis of the human resource government area: (i) gradual raising costs in payroll, allied to (ii) huge raising inefficiency in public services, and (iii) civil servants are unprepared to improve better responses to currents citizen demands and to adopt new methods of management based on the best professional performance and the best quality of public services. We have concluded that the federal government often tries to make civil servants redundant instead of adopting a real policy of management that would give them better conditions to improve their performance. This paper presents a concrete proposal to improve quality in civil servants performance by taking advantage of information technology and of our assumed country¿s democratization. We suggest that the Brazilian state reform must be and should be a new path of social growth and development not only in economic basis.